Factors Associated with Opioid Initiation in OEF/OIF/OND Veterans with Traumatic Brain Injury - Hudson, Teresa J (Pain Med, 2018)
OBJECTIVE: These analyses examined opioid initiation and chronic use among Iraq (OIF) and Afghanistan (OEF/OND) veterans with a new diagnosis of traumatic brain injury (TBI) in the Veterans Health Administration (VHA). METHODS: Data were obtained from national VHA data repositories. Analyses included OEF/OIF/OND veterans with a new TBI diagnosis in 2010–2012 who used the VHA at least twice, had not received a VHA opioid prescription in the 365 days before diagnosis, and had at least 365 days of data available after TBI diagnosis. RESULTS: Analyses included 35,621 veterans. Twenty-one percent initiated opioids; among new initiators, 23% used chronically. The mean dose was 24.0 mg morphine equivalent dose (MED) daily (SD = 24.26); mean days supplied was 60.52 (SD = 74.69). Initiation was significantly associated with age 36–45 years (odds ratio [OR] = 1.09, 95% CI = 1.01–1.17, P = 0.04), female gender (OR = 1.22, P < 0.001), having back pain (OR = 1.38, P < 0.0001), arthritis/joint pain (OR = 1.24, P < 0.0001), or neuropathic pain (OR = 1.415, P < 0.02). In veterans age 36–45 years, those living in small rural areas had higher odds of chronic opioid use (OR = 1.31, P < 0.0001, and OR = 1.33, P = 0.006, respectively) and back pain (OR = 1.36, P = 0.003). Headache/migraine pain was associated with decreased odds of chronic opioid use (OR = 0.639, P = 0.003). CONCLUSIONS: Prevalence of opioid use is relatively low among OEF/OIF/OND veterans with newly diagnosed TBI who are using VHA. Among those who initiated opioids, about 25% use them chronically. Prescribing was mostly limited to moderate doses, with most veterans using opioids for approximately two months of the 12-month study period.